PENANAMAN PRINSIP SEKSUALITAS ALKITABIAH KEPADA GENERASI Z YANG BERSEKSUALITAS CAIR: SEBUAH USULAN - Monalisa Ishakputro; Twin Yoshua R. Destyanto; Twin Hosea W. Kristyanto; Gabriel Ravena; Terry Kadarisman (The Way: Jurnal Teologi dan Kependidikan, 2022)
The existence of Generation Z (Gen-Z) is significant for the future of Indonesia. Gen-Z is characterized by being open-minded towards different views, technologically savvy, and having an informal communication style. These characteristics shape Gen-Z into a generation that is fluid in terms of sexuality. They are not hesitant to support and even embrace issues related to LGBT, i.e., that a person determines his own sexuality without anyone being able to set criteria for that determination. This study aims to propose a strategy for cultivating the principles of biblical sexuality in Gen-Z. A qualitative method with a systematic literature study approach and in-depth interviews (to 4 informants) was chosen to answer these objectives. The review of the literature and in-depth interviews indicate that a friendly approach is required, in accordance with Gen-Z's way of digesting information, to instill a principle of truth. Through these facts, this study proposes a strategy to cultivate the principle of biblical sexuality which is characterized by dependence on the guidance of the Holy Spirit, disciple Gen-Z’s parents first, build sincere relationships with Gen-Z, and build a two-way bridge between clergy and the LGBT community. The stages are continued with the process of cultivating the biblical principle of sexuality to Gen-Z which must be carried out with friendly and authoritative characteristics.